3(x-1)=4(5+2x)

Simple and best practice solution for 3(x-1)=4(5+2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-1)=4(5+2x) equation:


Simplifying
3(x + -1) = 4(5 + 2x)

Reorder the terms:
3(-1 + x) = 4(5 + 2x)
(-1 * 3 + x * 3) = 4(5 + 2x)
(-3 + 3x) = 4(5 + 2x)
-3 + 3x = (5 * 4 + 2x * 4)
-3 + 3x = (20 + 8x)

Solving
-3 + 3x = 20 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-3 + 3x + -8x = 20 + 8x + -8x

Combine like terms: 3x + -8x = -5x
-3 + -5x = 20 + 8x + -8x

Combine like terms: 8x + -8x = 0
-3 + -5x = 20 + 0
-3 + -5x = 20

Add '3' to each side of the equation.
-3 + 3 + -5x = 20 + 3

Combine like terms: -3 + 3 = 0
0 + -5x = 20 + 3
-5x = 20 + 3

Combine like terms: 20 + 3 = 23
-5x = 23

Divide each side by '-5'.
x = -4.6

Simplifying
x = -4.6

See similar equations:

| xxx=64 | | 0.2(x+3)-4(2x+3)=0.9 | | 1.5(x-1)=x+3 | | 2x^2-23x+57=0 | | 64r^2-9t^2=0 | | -36=6 | | -8-x/7=-8 | | -7r-21=-63 | | 4x=36+4x | | 100=45+14.99x | | 17+3x=28x-28 | | 8.2+(-1.5)=k | | -39=-3(-3m+7) | | 8x-8=4x+3 | | 96=24a | | 8.2+(-1.5)= | | 3b-5b+6b= | | 12d+2-3d= | | 1706=110x+56 | | z^30+275=1225 | | -3a-(-12)=19 | | 62x+9=5x+8 | | k=8.2+(-1.5) | | 4x^2-4x=11 | | 211,200=660w | | [(8-y)+(3y+4y)]+2= | | -27=.75w | | 5b=a-c | | -6d=42 | | 8=3-2n | | 5x-3=5(x+1) | | (x-4)(x^2+4x+16)= |

Equations solver categories